The satisfaction of contraception in today’s female university students - West, Alexandra L.; Sladyk, Karen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The misuse and discontinuation of contraception is becoming common. This leads to an increase of unintended sexually transmitted infections (STIs) or pregnancies. Literature showed negative side effects, relationships and insufficient healthcare access can decrease satisfaction leading to incorrect use or cessation of contraception. Methods: One hundred and one female university students were given an electronic survey to explore their feelings and opinions towards contraception. Results: Results showed there were several correlations between method of choice, pregnancy concerns, overall satisfaction, and the strengths and limitations of contraceptive use. Qualitative data showed opposing views on the strengths and limitations of providers and health insurance companies. Conclusions: The findings based on both qualitative and quantitative data showed most women endure negative experiences and side effects of contraception for the prevention of pregnancy. Future research should focus on increasing satisfaction by enhanced counselling efforts and decreasing the negative effects experienced.